Catalytic Polymerization of Acrylonitrile by Khulays Bentonite - Matar M. Al-Esaimi (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2007)
The aqueous polymerization of acrylonitrile (AN) catalyzed with exchanged Khulays bentonite . The influence of various polymerization parameters ( e.g., concentrations of Potassium Persulfate (K2S2O8) and monomer , various of organic solvents, and different temperature has been investigated. It was found that the rate of polymerization of AN was found to be dependent on monomer concentration, initiator and temperature. The activation energy of polymerization was calculated .Thermal properties of the polymer were studied by TGA and DSC techniques. © 2007 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0)